2017
DOI: 10.1155/2017/2953930
|View full text |Cite
|
Sign up to set email alerts
|

Stigmasterol Modulates Allergic Airway Inflammation in Guinea Pig Model of Ovalbumin-Induced Asthma

Abstract: We explored the potential benefits of stigmasterol in the treatment of asthma, an airway disorder characterized by immune pathophysiology and with an ever-increasing worldwide prevalence. We assessed the modulatory effect of the intraperitoneal administration of stigmasterol on experimentally induced airway inflammation in guinea pigs. The effect of stigmasterol on inflammatory cell proliferation, oxidative stress, lung histopathology, and remodeling was investigated. The results showed significant suppressive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 33 publications
6
43
0
Order By: Relevance
“…Thus, the present study successfully induced AA in mice after treatment with OVA. Inflammatory reactions play important roles in the development of AA, and various studies have demonstrated that the alleviation of inflammatory reactions is a useful way to treat asthma [12,13]. The present results demonstrate that MXDT inhibits inflammatory reactions in lung tissues of mice with OVA-induced AA.…”
Section: Discussionsupporting
confidence: 68%
“…Thus, the present study successfully induced AA in mice after treatment with OVA. Inflammatory reactions play important roles in the development of AA, and various studies have demonstrated that the alleviation of inflammatory reactions is a useful way to treat asthma [12,13]. The present results demonstrate that MXDT inhibits inflammatory reactions in lung tissues of mice with OVA-induced AA.…”
Section: Discussionsupporting
confidence: 68%
“…Stigmasterol is a steroid alcohol with immune-modulatory properties either alone or as a component of phytosterol mixtures [31]. It was reported to attenuate both innate and adaptive immune responses, and inhibit in ammatory cell recruitment and oxidative stress as well [15,32]. Rhein a major component of many medicinal herbs with various properties, including anti-in ammatory, antioxidant and anticancer activities [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…We have developed a guinea pig model of IAR and LAR through the inhalation of antigen OVA in OVA-sensitized guinea pigs. The guinea pig has generally been chosen as an experimental animal because of histological similarities that exist between lungs of antigen exposed guinea pigs and asthmatic lungs in human because this species can exhibit early and late-phase airway obstruction, bronchial eosinophilia and increased airway reactivity following exposure of sensitized animals to antigen in the putative involvement of chemical mediator, cytokines and inflammatory cells on the development of LAR, compared to other species such as mouse, rat, primate or rabbit [ 4 19 ]. Furthermore, the double-chambered plethysmograph system for restrained guinea pigs in this study has been specially developed for the investigation of bronchospasm-molytically active substances on a conscious animal, and it has been proven as a reliable and standard method in the study of pulmonary functions in a non-invasive approach.…”
Section: Discussionmentioning
confidence: 99%